2022
DOI: 10.1111/1475-6773.13954
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of certified nursing assistants and administrators on staffing the nursing home frontline during the COVID‐19 pandemic

Abstract: Objective To identify best practices to support and grow the frontline nursing home workforce based on the lived experience of certified nursing assistants (CNAs) and administrators during COVID‐19. Study setting Primary data collection with CNAs and administrators in six New York metro area nursing homes during fall 2020. Study design Semi‐structured interviews and focus groups exploring staffing challenges during COVID‐19, strategies used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…This analysis focused specifically on the challenges identified by CNAs and administrators posed by this novel, stressful experience to inform future supports for the workforce. Findings on adaptations and needed resources were reported separately ( Franzosa et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis focused specifically on the challenges identified by CNAs and administrators posed by this novel, stressful experience to inform future supports for the workforce. Findings on adaptations and needed resources were reported separately ( Franzosa et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…Staff reported a positive impact on job satisfaction and resident quality of life. These findings are particularly relevant given challenges with staff retention in NHs exacerbated by the COVID‐10 pandemic 7 . Increasing the use of smart tablets in NHs may be one approach to improving staff satisfaction as well as increasing real‐time access to online clinical support tools.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are particularly relevant given challenges with staff retention in NHs exacerbated by the COVID-10 pandemic. 7 Increasing the use of smart tablets in NHs may be one approach to improving staff satisfaction as well as increasing realtime access to online clinical support tools. Also, more than half of staff indicated that NH residents were proficient in using a tablet, though many residents did require training from staff to use tablets.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Research documenting the impact of the pandemic to date is largely quantitative, relies on one-time surveys with nursing home administrators or staff, or is limited to one location. [21][22][23] Beyond what we know from existing quantitative research, this knowledge does not capture the actual and potential depth of experiences and perspectives of the COVID-19 crisis in nursing homes. Our qualitative research helps to fill this gap, through repeated, semi-structured, indepth interviews with nursing home administrators across the country, conducted over the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Research documenting the impact of the pandemic to date is largely quantitative, relies on one‐time surveys with nursing home administrators or staff, or is limited to one location 21–23 . Beyond what we know from existing quantitative research, this knowledge does not capture the actual and potential depth of experiences and perspectives of the COVID‐19 crisis in nursing homes.…”
Section: Introductionmentioning
confidence: 99%